2020
DOI: 10.1155/2020/7395187
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin Attenuates Myocardial Ischemia/Reperfusion Injury via Downregulating Oxidative Stress and NLRP3 Inflammasome Pathway in Mice

Abstract: Oridonin (ORI), the major pharmacological component extracted from a traditional Chinese medicine, possesses a beneficial effect on myocardial ischemia/reperfusion (I/R) injury. However, the underlying molecular mechanism by which ORI effects take place is not completely known. Thus, whether ORI works via downregulating oxidative stress and nod-like receptor protein-3 (NLRP3) inflammasome pathway was investigated in this study. Mice underwent surgery to induce myocardial I/R injury, and some were administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Oridonin inhibited the expression of TXNIP, NLRP3, and cleaved caspase-1 induced by CUMS, suggesting a possible mechanism for the anti-depression effects of oridonin. A similar effect of oridonin was found in mice with myocardial ischemia/reperfusion (I/R) injury [10]. Oridonin alleviated I/R induced myocardial injury by inhibiting oxidative stress and the NLRP3 inflammasome pathway [10].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Oridonin inhibited the expression of TXNIP, NLRP3, and cleaved caspase-1 induced by CUMS, suggesting a possible mechanism for the anti-depression effects of oridonin. A similar effect of oridonin was found in mice with myocardial ischemia/reperfusion (I/R) injury [10]. Oridonin alleviated I/R induced myocardial injury by inhibiting oxidative stress and the NLRP3 inflammasome pathway [10].…”
Section: Discussionmentioning
confidence: 81%
“…A similar effect of oridonin was found in mice with myocardial ischemia/reperfusion (I/R) injury [10]. Oridonin alleviated I/R induced myocardial injury by inhibiting oxidative stress and the NLRP3 inflammasome pathway [10].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…As reported by researches in recent years, oridonin exhibited beneficial influences on cardiovascular disease. In a myocardial ischemia-reperfusion injury mouse models, down-regulation of oxidative stress and NLRP3 inflammation has been shown to mitigative effect of oridonin to myocardial ischemia reperfusion injury ( Lu et al, 2020 ). Similar results have been verified by researchers from the perspective of metabonomics ( Zhang J. et al, 2019 ).…”
Section: Pharmacologymentioning
confidence: 99%
“…Several data are showed that in an NLRP3 inflammasome-dependent manner oridonin exerts therapeutic effects on myocardial ischemia, liver fibrosis, neuroinflammation, colitis and sepsis. Also, there are reports that oridonin reduces lung inflammation and improves survival in SARS-CoV-infected animals [ [127] , [128] , [129] , [130] , [131] ]. The mechanism of oridonin action is based on the suppression of NF-κB or MAPK activity and inhibition of inflammasome-independent pro-inflammatory cytokines releases, such as TNF-α and IL-6 [ 132 ].…”
Section: Substances That Can Inhibit Inflammasome Activitymentioning
confidence: 99%